Ectoparasites and Hemoparasites of the Silvery Mole Rats (Heliophobius Argentiocinereus Emini) In Morogoro Region, Tanzania (Journal of Ideas in Health, 2025)
Background: The silvery mole rat (Heliophobius Argentiocinereus Emini) is a subterranean rodent widely distributed across Sub-Saharan Africa and exploited as a protein source in some communities. Despite this, limited data exist on ectoparasite and hemoparasite infections in this species in Tanzania. This study aims to determine the prevalence of hemoparasites in silvery mole rats and to identify their potential arthropod vectors in the Morogoro region of Tanzania. Methods: A cross-sectional study was conducted in Mvomero and Morogoro districts, Tanzania, between March and June 2023. A total of 137 silvery mole rats were captured through manual excavation. Ectoparasites were collected from animal fur and identified morphologically using taxonomic keys. Blood samples were obtained directly from the heart, and smears were prepared, stained with Giemsa, and microscopically examined for hemoparasites. Statistical analysis was performed to assess associations between host factors, ectoparasite infestation, and hemoparasite infection.Results: Of the 137 captured mole rats, 65% (n=89) were females and 86.7% (n=120) were adults. The overall prevalence of ectoparasitism was 71.5% (98/137). A total of 1,503 ectoparasites were recovered, dominated by Androlaelaps spp. (93.15%, n=1400), followed by Echinolaelaps echidinus (6.19%, n=93), and Haemaphysalis spp. ticks (0.67%, n=10). Hemoparasites were detected in 29.2% (40/137) of hosts, including Anaplasma spp. (25.5%) and Babesia spp. (16.8%). Coinfections with both parasites occurred in 13.1% of individuals. Adult mole rats had significantly higher odds of hemoparasite infection (OR = 3.23, 95% CI: 1.15–9.11, p = 0.04). Tick infestation was strongly associated with Babesia spp. (χ² = 11.91, OR = 15.56, p < 0.001) and Anaplasma spp. (χ² = 5.82, OR = 8.3, p = 0.01).Conclusion: This study demonstrates a high prevalence of ectoparasites and hemoparasites among silvery mole rats in the Morogoro region. The dominance of mite infestations and significant associations between ticks and blood parasites highlight the potential role of mole rats as reservoirs of zoonotic pathogens. Further molecular studies are warranted to characterize these parasites and evaluate their public health implications.
Keywords: Silvery Mole Rat, Heliophobius Argentiocinereus Emini, Ectoparasites, Hemoparasites, Anaplasma, Babesia, Prevalence; Zoonotic Diseases, Tanzania